SISTEM DETEKSI AKTIVITAS BERBAHAYA PADA SERVER MENGGUNAKAN CROWDSEC - Ridha, Muhammad Arif Fadhly; Maheswara, Galih Ihsan (Politeknik Caltex Riau, 2025)
The rapid development of technology has driven almost all business sectors to adopt digital operations, but this shift has also increased the risk of cybercrime, targeting systems and data. Cyber Threat Intelligence (CTI) is a cybersecurity approach that involves collecting, analyzing, and understanding data to identify the motives, targets, and attack patterns of cybercriminals. One solution to address these threats is CrowdSec, an open-source software designed to detect and prevent cyber-attacks in various environments, including servers. Testing results demonstrate that CrowdSec is effective in detecting SSH brute-force, port scanning, and SQL injection attacks. By identifying suspicious attack patterns and blocking attackers' IPs, CrowdSec significantly reduces the risk of server damage. Its response times are fast: 23 seconds for SSH brute-force, 10 seconds for port scanning, and 6 seconds for SQL injection. Compared to Fail2Ban, CrowdSec offers greater configuration flexibility and broader attack detection capabilities, supported by the CrowdSec Hub, which provides a variety of attack scenarios. With its simple installation and configuration process, CrowdSec is an ideal choice for enhancing server security.